Preliminary Evidence for IL-10-Induced ACE2 mRNA Expression in Lung-Derived and Endothelial Cells: Implications for SARS-Cov-2 ARDS Pathogenesis - Albini, Adriana; Calabrone, Luana; Carlini, Valentina; Benedetto, Nadia; Lombardo, Michele; Bruno, Antonino; Noonan, Douglas M. (Frontiers in Immunology, 2021)
Angiotensin-converting enzyme 2 (ACE2) is a receptor for the spike protein of SARS-COV-2 that allows viral binding and entry and is expressed on the surface of several pulmonary and non-pulmonary cell types, with induction of a “cytokine storm” upon binding. Other cell types present the receptor and can be infected, including cardiac, renal, intestinal and endothelial cells. High ACE2 levels protect from inflammation. Despite the relevance of ACE2 levels in COVID-19 pathogenesis, experimental studies to comprehensively address the question of ACE2-regulations are still limited. A relevant observation from the clinic is that, besides the pro-inflammatory cytokines, such as Il-6 and Il-1, also the anti-inflammatory cytokine IL-10 is elevated in worse prognosis patients. This could represent somehow a “danger signal”, an alarmin from the host organism, given the immuno-regulatory properties of the cytokine. Here, we investigated whether IL-10 could increase ACE2 expression in the lung-derived Calu-3 cell line. We provided preliminary evidence of ACE2 mRNA increase in cells of lung origin in vitro, following IL-10 treatment. Endothelial cell infection by SARS-COV-2, is associated with vasculitis, thromboembolism and disseminated intravascular coagulation. We confirmed ACE2 expression enhancement by Il 10 treatment also on endothelial cells. The sartans (olmesartan, losartan) showed non-statistically significant ACE2 modulation in Calu-3 and HUVE cells, as compared to untreated control cells. We observed that the antidiabetic biguanide metformin, a putative anti-inflammatory agent also upregulates ACE2 expression in Calu-3 and HUVEC cells. We hypothesized that IL-10 could be a danger signal and its elevation could possibly represent a feed-back mechanism fighting inflammation. Although further confirmatory studies are required, inducing IL-10 upregulation could be considered as a novel approach to treat COVID-19 associated acute respiratory distress syndrome (ARDS) and vasculitis, by reinforcing ACE2 levels.